Penerapan Maksim Kebijaksanaan dalam Interaksi Sosial di Kelurahan Pelutan, Kecamatan Pemalang, Kabupaten Pemalang - Tania Safitri; Leli Triana; Vita Ika Sari (Peneliti.net, 2020)
In social interaction in the community, aside from paying attention to politeness, the application of politeness principles in speaking among maxims of wisdom must be applied. This study aims to determine the form of the application of the maxim of wisdom in social interaction, the data of this research are the speech of the young generation of Pelutan Village, Pemalang District, Pemalang Regency when conducting Social Interaction. The source of the data in this study is the young generation of Pelutan Village, Pemalang District, Pemalang Regency. The method used in this research is descriptive qualitative method, the purpose of using this method is to describe the application of wisdom maxim in the social interaction of young generation in Pelutan Village, Pemalang District, Pemalang Regency. In the application of wisdom maxim in young social interaction between Pelutan Village, Pemalang District, Pemalang District there are five processes namely, the application of the maxim of the cooperative associative process policy, the application of the maxim of the policy of the Associative Accommodation process, the Competition Dissociative process, the application of the policy maxim of the Dissociative Process of Contravention, the application of the maxim discretionary dissociative process.